Cortical and Trabecular Bone Microstructure Did Not Recover at Weight‐Bearing Skeletal Sites and Progressively Deteriorated at Non‐Weight‐Bearing Sites During the Year Following International Space Station Missions. (28th June 2017) - Vico, Laurence; van Rietbergen, Bert; Vilayphiou, Nicolas; Linossier, Marie‐Thérèse; Locrelle, Hervé; Normand, Myriam; Zouch, Mohamed; Gerbaix, Maude; Bonnet, Nicolas; Novikov, Valery; Thomas, Thierry; Vassilieva, Galina
ABSTRACT: Risk for premature osteoporosis is a major health concern in astronauts and cosmonauts; the reversibility of the bone lost at the weight‐bearing bone sites is not established, although it is suspected to take longer than the mission length. The bone three‐dimensional structure and strength that could be uniquely affected by weightlessness is currently unknown. Our objective is to evaluate bone mass, microarchitecture, and strength of weight‐bearing and non‐weight‐bearing bone in 13 cosmonauts before and for 12 months after a 4‐month to 6‐month sojourn in the International Space Station (ISS). Standard and advanced evaluations of trabecular and cortical parameters were performed using high‐resolution peripheral quantitative computed tomography. In particular, cortical analyses involved determination of the largest common volume of each successive individual scan to improve the precision of cortical porosity and density measurements. Bone resorption and formation serum markers, and markers reflecting osteocyte activity or periosteal metabolism (sclerostin, periostin) were evaluated. At the tibia, in addition to decreased bone mineral densities at cortical and trabecular compartments, a 4% decrease in cortical thickness and a 15% increase in cortical porosity were observed at landing. Cortical size and density subsequently recovered and serum periostin changes were associated with cortical recovery during the year after landing. However, tibial cortical porosity or trabecular bone failed to recover, resulting in compromised strength. The radius, preserved at landing, unexpectedly developed postflight fragility, from 3 months post‐landing onward, particularly in its cortical structure. Remodeling markers, uncoupled in favor of bone resorption at landing, returned to preflight values within 6 months, then declined farther to lower than preflight values. Our findings highlight the need for specific protective measures not only during, but also after spaceflight, because of continuing uncertainties regarding skeletal recovery long after landing. © 2017 American Society for Bone and Mineral Research.